Pengaruh penggunaan substrat sintetik dengan bahan dasar yang berbeda terhadap produktivitas cacing sutra (Tubifex sp.) - Setiadi, Ai; Suhardi, Muhammad Tegar Alif Suhardi; Rahardjo, Sinung; Nurraditya , Lakonardi; Sektiana, Sinar Pagi (Universitas Sam Ratulangi, 2025)
The need for high-quality natural feed for fish farming and aquaculture industry is increasing along with the rapid growth of the fisheries sector worldwide. However, the problem faced is the great dependence on the availability of worms from nature so that silk worm cultivation is very important to ensure the availability of quality natural feed for fish farming. This study aims to determine the effect of the use of synthetic substrates made from different materials on the productivity and absolute weight growth of silk worms, as well as to determine the effectiveness of harvesting in each treatment and business analysis. This experiment was designed in a completely randomized design (CRD) with 3 treatments which are: P1 (Cotton substrate), P2 (Net substrate), and K (as control). Each treatment was quadriplicated and the data analysis was run in One-way ANOVA for CRD. Worms were kept for 30 days with the results of silk worm productivity. The highest productivity figures were in P2 with a value of 689.48 ± 52.80 g / m2 / cycle and K 622.52 ± 121.60 g / m2 / cycle. Statistical tests showed that there was no significant effect (sig.>0.05) of substrate use on silkworm productivity. Absolute weight growth K 12.75±12.25 g/m2/cycle, P1 13.5±7.59 g/m2/cycle, P2 19.5±5.32 g/m2/cycle. Water quality parameters during the study period ranged from optimal values. Business analysis was assumed and the results of the business analysis obtained were loss and not feasible. It can be concluded that the synthetic substrate used did not provide significant benefits in silkworm cultivation. Keywords: Silkworms, Substrate Synthesis, Productivity